A directional distance function approach for identifying the input/output status of medical residents. Issue 9 (19th February 2018) - Ferrier, Gary D.; Leleu, Hervé; Valdmanis, Vivian G.; Vardanyan, Michael
ABSTRACT: Previous empirical studies examining the impact medical residents have on hospital productivity have made a priori assumptions about whether medical residents are inputs (labour providing patient care) or outputs (students receiving mandatory training under the supervision of an attending physician) when specifying their estimating equations. We shed light on the role medical residents play in hospital production by using a data-driven parametric approach based on the directional technology distance function. Our primary goal is to assess the extent to which one of the two roles of medical residents empirically dominates the other and to see whether the role varies across different types of hospital. Using the American Hospital Association data from 1994 to 2010, we find that residents are inputs in all rural and public non-teaching hospitals, but they are outputs in urban-area not-for-profit teaching hospitals. We also demonstrate that the status of residents is related to the case-mix index and can vary with hospital size.